PENERAPAN METODE TEAM QUIZ UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS IV PADA MATA PELAJARAN PAI - Taufik Mustofa, Iqbal Amar Muzaki, Hinggil Permana (Universitas Islam Madura, 2021)
Researchers conducted class action research using team quiz model. This is done so that students can learn actively. After that, it is expected that after completing the learning with the application of team quiz model, researchers are aware of the improvement of students' cognitive learning outcomes at SDN Tenjolaya Cicalengka, especially grade IV. This research was conducted by class action (PTK) research method; i.e. efforts to improve the quality of learning in improving the quality of learning by performing practical actions as well as reflective. The process of collecting data with technical observation between teachers and students. A total of 28 students consisting of 14 female students and 14 male students of grade IV SDN Tenjolaya were the objects in this study. The results showed that the implementation of this Team quiz method was well organized. This can be seen from the increase in the average student's learning score in each cycle. With this team quiz method, in the first cycle the results (grades) learn the cognition of students at an average of 66, 25. In the second cycle the results (grades) of learning cognition of students increased significantly because it was suspected that the attitude of seriousness of students increased so that the average score of students obtained 82.67. Based on that, this team quiz method is considered suitable for use in PAI learning process.